Análisis Interference B1 dan Penggunaan Teknologi dallas Penalizan Skripsi Berbahasa Inggris - Lao, Yandres Answo Djedelbert; Weda, Sukardi; Basri, Muhammad (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2026)
This study examines factors influencing first language interference in students’ English thesis writing at a state university in North Central Timor Regency, East Nusa Tenggara. The study employed a qualitative approach using purposive sampling involving thesis supervisors who guided more than one student. Data were collected through semi-structured in-depth interviews and analyzed through data condensation, data display, and conclusion drawing. The findings revealed several factors contributing to first language interference, i.e: a) patterns of English construction and technology mediation used by students; and b) mismatch between the supervisors' educational backgrounds and the institution's assignments and the students' research topics. The study demonstrates that linguistic interference should not be viewed solely from a micro-linguistic perspective, but also from broader dimensions involving supervisors’ competencies, experiences, and institutional policies. The findings imply the need for better alignment between lecturers’ academic expertise, supervisory assignments, and institutional decision-making processes to reduce interference issues in students’ academic writing.